Timely Immunization Series Completion among Children of Immigrants - Buelow, Victoria H. (2008)
This study examines the relationship between timely immunization series completion among children of immigrants and parental nativity, residential duration in the United States, and citizenship status. We analyzed data from the childhood immunization supplement of the 2000–2003 National Health Interview Surveys (NHIS). Combined 4:3:1:3:3 immunization series completion by 18 months of age served as the dependent variable. Nested logistic regression models were estimated to examine relationship between parental nativity and timely immunization completion. Although socio-economic and health care access partially explained parental nativity, citizenship, and residential duration differences in timely completion, having a foreign-born mother was associated with a 14% reduced odds of completing the combined series on time when compared to children with US-born mothers net of covariates. Children of non-citizen mothers who had resided in the country for less than 5 years were the least likely to complete immunizations on time. The elimination of disparities in timely immunization completion among children requires special attention to children of newly arrived and non-citizen immigrants.